Domestic Water and Sanitation in Kerala A Situation Analysis - Rajeevan Chakrapani (Forum for Policy Dialogue on Water Conflicts in India, 2014)
Kerala’s population density is one of the highest in the world. It is one of the smallest states in India encompassing only 1.3% of the total area of the country. However, it has a high population density, at 747 persons per sq. km, which is much higher than the national average of 267 persons per sq. km. The people in the state prefer a dispersed settlement pattern. Hence, the state requires large areas of land for housing. Residents of Kerala prefer houses on independent plots. This has resulted in large scale land reclamation. Blessed with an abundance of rainfall, about 3,000 mm annually, Kerala has 44 monsoon-fed rivers, of the shortest of which flows for 15 km. However, due to the undulating topography of the state, run-off is also quite high. This has resulted in an increased demand for water resources and acute shortages